2014
DOI: 10.3389/fmicb.2014.00464
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial targets localize to the extracellular vesicle-associated proteome of Pseudomonas aeruginosa grown in a biofilm

Abstract: Microbial biofilms are particularly resistant to antimicrobial therapies. These surface-attached communities are protected against host defenses and pharmacotherapy by a self-produced matrix that surrounds and fortifies them. Recent proteomic evidence also suggests that some bacteria, including the opportunistic pathogen Pseudomonas aeruginosa, undergo modifications within a biofilm that make them uniquely resistant compared to their planktonic (free-living) counterparts. This study examines 50 proteins in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 95 publications
(118 reference statements)
3
29
0
Order By: Relevance
“…A recent proteomic analysis of OMVs obtained from planktonic growth and biofilm in Pseudomonas aeruginosa revealed that drug-binding proteins (notably efflux proteins) were more concentrated in the biofilm OMVs. It is another example of possible involvement of the vesicles in antibiotic resistance (Park et al, 2014 ).…”
Section: Involvement Of the Vesicles In Antibiotic Resistancementioning
confidence: 99%
“…A recent proteomic analysis of OMVs obtained from planktonic growth and biofilm in Pseudomonas aeruginosa revealed that drug-binding proteins (notably efflux proteins) were more concentrated in the biofilm OMVs. It is another example of possible involvement of the vesicles in antibiotic resistance (Park et al, 2014 ).…”
Section: Involvement Of the Vesicles In Antibiotic Resistancementioning
confidence: 99%
“…Pseudomonas represents the phenomenon of resistance to antibiotics, as it is difficult to address the injuries caused by the drug resistance in this type of bacteria, as it possesses natural resistance, including changing the permeability of the outer wall, and the possession of several groups of stream systems, Pseudomonas aeruginosa also produces many enzymes responsible for the decomposition of many antimicrobials, especially Metallo ß-Lactamases (MßLs), Extended Spectrum Beta-Lactamases (ESßLs), and Ampler Molecular Class (AMPC) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The MV-related proteins identified were OM enzymes and proteins involved in the transport of small molecules, the uptake of iron and antibiotic resistance (Couto et al, 2015). In addition, vesicles purified from late-stage P. aeruginosa biofilms are enriched for drug-binding proteins, which makes the bacterial species inside these biofilms even better protected against antibiotics (Park et al, 2014). It has been suggested further that MVs secreted by P. aeruginosa are under the control of the quorum sensing system and supply the forming biofilm with extracellular DNA (eDNA) and LPS (Nakamura et al, 2008).…”
Section: Mvs In Biofilmmentioning
confidence: 99%